2022
DOI: 10.1097/md.0000000000031891
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acupuncture in the treatment of occipital neuralgia: A systematic review and meta-analysis

Abstract: Background: Acupuncture is used to treat subjects with occipital neuralgia, which is 1 of the main causes of occipital pain; however, its effect is conflicting. Hence, the current study aims to evaluate the effects of acupuncture in the treatment of occipital neuralgia.Methods: In a systematic search of PubMed, Embase, OVID, China National Knowledge Infrastructure, Cochrane Library, Chinese Biomedical Literature Database, Wanfang databases, and Google Scholar until July 2021, 15 studies aimed to evaluate the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Additionally, few serious adverse events have been reported [10]. Two previous systematic reviews (SRs) have examined the role of acupuncture on and revealed that acupuncture treatment (either acupuncture alone or in combination with other therapies compared with control therapies) was generally associated with improved pain symptoms and better effective rate (ER) [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, few serious adverse events have been reported [10]. Two previous systematic reviews (SRs) have examined the role of acupuncture on and revealed that acupuncture treatment (either acupuncture alone or in combination with other therapies compared with control therapies) was generally associated with improved pain symptoms and better effective rate (ER) [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…First, these previous studies had several limitations. One study included (a) patients with postherpetic neuralgia and migraine as well as ON, which limit the generalizability of the findings, and (b) non-randomized trials, as well as randomized controlled trials (RCTs), which hinder causal inference [11]. Another study had an ideal methodology and impressive results, but it included most recent RCT was published in 2016 [12].…”
Section: Introductionmentioning
confidence: 99%